2016
DOI: 10.7243/2053-3640-4-1
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients treated with radiofrequency ablation for thyroid nodules

Abstract: Background: Many studies have reported mean reductions in nodule volumes and described improvements in the sense of pressure and aesthetic symptoms after radiofrequency ablation. The aim of our study was to document changes in quality of life by means of a 13-scale questionnaire named ThyPRO in a cohort of patients treated with radiofrequency ablation for benign thyroid nodules. Moreover, we assessed the efficacy and safety of the procedure and correlations between efficacy and some features both of the treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Other symptom scales also improved persistently in both groups. By contrast, a previous study by Oddo et al [ 13 ] reported no significant improvement in QoL scales after RFA, except for the "general score," which improved after 3 months. They explained that the cause of less improvement seemed to have been due to the low VRR, which was <50% in most patients.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Other symptom scales also improved persistently in both groups. By contrast, a previous study by Oddo et al [ 13 ] reported no significant improvement in QoL scales after RFA, except for the "general score," which improved after 3 months. They explained that the cause of less improvement seemed to have been due to the low VRR, which was <50% in most patients.…”
Section: Discussionmentioning
confidence: 64%
“…All US systems were equipped with a high-frequency linear probe (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Three orthogonal diameters, the longest diameter and two perpendicular diameters, were measured, and the volume of each nodule was calculated using the equation as follows: V = πabc/6…”
Section: Preprocedural Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group recently published a study on changes in QoL, as assessed by means of ThyPRO after RFA of benign thyroid nodules. In that study, we did not find a significant improvement in ThyPRO scales, except for the “general score,” which improved after three months ( 32 ). The cause of less improvement of ThyPRO scales in this study ( 32 ) was probably induced by low volume reduction: the majority of patients showed less than a 50% volume reduction.…”
Section: Discussionmentioning
confidence: 76%